Scalability Techniques for Practical Synchronization Primitives. - BUESO, DAVIDLOHR (Communications of the ACM, 2015)
The article looks at synchronization primitives, or locks, which allow for concurrent execution of multiple threads through the use of a mutual exclusion concurrency control policy. It indicates that poorly designed locks can cause performance problems as software applications are scaled up for use in larger systems. The author discusses improvements that have been made in locks in the Linux operating system. Topics include hybrid locking models and factors that account for lock performance including granularity and the ratio of read-only to other data regions.